Advanced statistical methods for detecting the Epoch of Reionisation - Cook, Jaiden Hue (Curtin University, 2023)
This thesis investigates the widefield foreground contamination on the expected 21cm power spectrum, by modelling these sources with multi-component 2D Gaussians. Additionally, we calculate the skew spectrum for a set of seven cosmological 21cm simulations, characterising how the higher order statistic changes with respect to the X-ray heating and ionisation topologies. We then develop an analytical framework for estimating the interferometric skew spectrum, applying this to realistic foreground models, and to a fiducial 21cm simulation.